High‐Throughput Micromechanical Testing Enabled by Optimized Direct Laser Writing. Issue 7 (3rd April 2023) - Jelinek, Alexander; Zak, Stanislav; Alfreider, Markus; Kiener, Daniel
Abstract : The cover shows a photomontage of 3D‐prints via two‐photon‐lithography. To the lower left, a model of an iconic building of Leoben is shown (base width: 1.1 mm). In the background and inset, optimized push‐to‐pull geometries incorporating double edge‐notched tension specimens (base width: 50 μm) for miniaturized fracture experiments are depicted. Details on are outlined by Alexander Jelinek and co‐workers in article number 2200288 .